1981
DOI: 10.1007/bf00554663
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hepatic cirrhosis and end-stage renal disease on pharmacokinetics and pharmacodynamics of furosemide

Abstract: After rapid intravenous injection of furosemide 40 mg (Fu), plasma levels were determined in 7 healthy volunteers, 8 patients with liver cirrhosis with ascites and 7 patients with end-stage renal disease (ESRD). The diuretic response was evaluated by measuring the urinary excretion of sodium and potassium and the urine volume. The mean elimination half life (t 1/2 beta) of Fu averaged 51 +/- 7.7 (+/- SD) min in healthy subjects, 52 +/- 7.7 min in cirrhosis and 200 +/- 57 min in ESRD. The non-renal clearance (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
5

Year Published

1982
1982
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(22 citation statements)
references
References 22 publications
0
17
0
5
Order By: Relevance
“…5 The mechanisms of resistance to furosemide have been evaluated in cirrhotic patients with ascites in several studies reported over the last 20 years. [6][7][8][9] It is now well recognized that furosemide pharmacokinetics are not altered by cirrhosis. The reduction in pharmacodynamic response, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…5 The mechanisms of resistance to furosemide have been evaluated in cirrhotic patients with ascites in several studies reported over the last 20 years. [6][7][8][9] It is now well recognized that furosemide pharmacokinetics are not altered by cirrhosis. The reduction in pharmacodynamic response, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal Na Ă· hyperreabsorption in diseases with reduced effective arterial blood volume, EABV Diseases presenting a "depressed" dose-response curve or resistance to diuretics include congestive heart failure (CHF) [2], decompensated cirrhosis of the liver [9], and nephrotic syndrome [10]. The common denominator of these disease entities is the reduced "effective arterial blood volume" (EABV), in which the relationship between cardiac output (CO) and peripheral vascular resistance dictates the filling of the arterial vascular tree [26,27].…”
Section: Dose-response Relationships For Diureticsmentioning
confidence: 99%
“…For example, studies on frusemide disposition are contradictory. Some indicate impairment of frusemide elimination (Fuller et al, 1981;Sawhney et al, 1981) whereas others have found no change (Allgulander et al, 1980;Keller et al, 1981;Verbeeck et al, 1982). More importantly, none of these studies have shown a clinically important reduction in frusemide clearance.…”
Section: Discussionmentioning
confidence: 98%